Unsur Budaya dalam Naskah “Wawacan Suluk Ki Ganda jeung Ki Sari” - Deni Abdul Ghoni; Yeni Herlina; Yayat Sudaryat (Badan Pengembangan dan Pembinaan Bahasa, 2024)
This research aims to describe the cultural elements in the Wawacan Suluk Ki Ganda jeung Ki Sari manuscript, which generally contains matters of Islamic monotheism. This research uses a descriptive qualitative approach with literature and document study methods. Data sources in the form of WSKGKS manuscripts were obtained from the National Library of Indonesia website with the number Plt. Plt 36 case 121. Then, the data was obtained using the seven elements of culture according to Koentjaraningrat. Of the seven cultural elements studied, only six elements appear in this manuscript, which include 1) religious system, 2) organizational system, 3) knowledge system, 4) language, 5) art, and 6) technology system, while the livelihood system does not appear at all. From the analysis of each of these cultural elements it shows that the elements or cultural systems that emerge are very attached and wrapped in Islamic principles. AbstrakPenelitian ini bertujuan untuk mendeskripsikan unsur budaya yang ada dalam naskah Wawacan Suluk Ki Ganda jeung Ki Sari (WSKGKS) yang secara umum memuat perihal ketauhidan agama Islam. Penelitian ini merupakan penelitian kualitatif deskriptif dari pemanfaatan langkah kerja filologi dan penggunaan teori tujuh unsur budaya menurut Koentjaraningrat. Sumber data berupa naskah WSKGKS yang didapatkan dari laman Perpustakaan Nasional RI dengan nomor Plt. Plt 36 peti 121. Dari tujuh unsur budaya yang diteliti, hanya enam unsur yang muncul dalam naskah ini, yaitu 1) sistem religi, 2) sistem organisasi, 3) sistem pengetahuan, 4) bahasa, 5) kesenian, dan 6) sistem teknologi, sedangkan sistem mata pencaharian tidak muncul sama sekali. Dari hasil analisis setiap unsur budaya tersebut terlihat bahwa unsur-unsur atau sistem-sistem kebudayaan yang muncul sangat melekat dan dibalut oleh prinsip keislaman.